Infrastructure State-Owned Enterprises A Tale of Inefficiency and Fiscal Dependence - Herrera Dappe, Matias (The World Bank, 2022)
This paper examines the performance of infrastructure companies owned by the state, using the newly created World Bank Database of Infrastructure State-Owned Enterprises (SOEs). The data cover 19 countries and 135 SOEs between 2000 and 2018. The analysis reveals that infrastructure SOEs are large and have weak financial performance that generates significant fiscal risk. The paper introduces new measures of financial performance net of fiscal transfers and examines previously uncovered patterns of subsidies by sector. It examines the effect of state ownership by comparing the firms in the database with hundreds of comparable private firms, using coarsened exact matching. The findings show that relative to comparable private firms, infrastructure SOEs are less efficient, represent a larger share of gross domestic product, have larger liabilities as a share of gross domestic product and larger employment costs as a share of revenues, and yield lower returns on assets